2013
DOI: 10.5812/ircmj.13896
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Population Studies Concerning Exposure to Pesticides in Iran: A Comprehensive Review

Abstract: Pesticides are widely used in Iranian agriculture and this has made a major toxicological concern among health professionals. The objective of this study is to explore national data about pesticides toxicity. All relevant databases such as Google Scholar, PubMed, and Scopus in a time period of 1960 to 2012 were searched for the keywords “Pesticides, Iran, Environment, and Population studies”. A total of 57 studies were found relevant and then included into study. Almost all non-experimental studies carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 55 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…Kalawat et al (2016) found that troponin I was elevated in 26% of studied patients after acute ALP toxicity and related this to myocardial damage by echocardiography not ECG changes. Mostafalou et al (2013) and Hakimoğlu et al (2015) are against our study as they reported that elevation of different cardiac enzymes such as CK-MB or troponin T (Tn T) levels could approve cardiotoxicity and indicate mortality but their absence couldn't exclude cardiotoxicity after acute phosphides exposure.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Kalawat et al (2016) found that troponin I was elevated in 26% of studied patients after acute ALP toxicity and related this to myocardial damage by echocardiography not ECG changes. Mostafalou et al (2013) and Hakimoğlu et al (2015) are against our study as they reported that elevation of different cardiac enzymes such as CK-MB or troponin T (Tn T) levels could approve cardiotoxicity and indicate mortality but their absence couldn't exclude cardiotoxicity after acute phosphides exposure.…”
Section: Discussionmentioning
confidence: 66%
“…The present study showed negative correlation between TAC and pulse. Anand et al (2011) and Mostafalou et al (2013) found that ALP toxicity caused tachycardia, decrease in catalase enzyme (antioxidant enzyme) but increase in superoxide dismutase (indicator of oxidative stress) among studied patients. Shakeri and Mehrpour (2015) study is against our findings as they found that ALP exposure caused bradycardia with oxidative stress and lipid peroxidation in experimental rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is commonly used for protection of stored grains in Asian and African countries. Because of its wide availability and free accessibility, it is commonly used in suicide attempts in some countries such as Iran, India, Morocco and Egypt (El-Naggar and El-Mahdy, 2011;Mostafalou et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides are some of the most important agents detected for poisoning and death in Iran through past decades. [2] Although M100 has been approved by agricultural institute of Iran for application in filed since 2012, we could not find any case report of M100 or STM poisoning in literature. We reported a case of M100 poisoning with hypoglycemia and revisable ST-elevation.…”
Section: Introductionmentioning
confidence: 88%